The HEMOLYSIS ACTIVITY OF BACTERIA ISOLATS FROM PELANGI FOREST OF IJEN GEOPARK - Arimurti, Sattya; Utarti, esti; sutoyo, sutoyo; siswanto, siswanto; Ayuningtyas, Tantri Raras (Department of Biology, Faculty Mahematics and Natural Sciences, University of Jember, 2023)
Ijen geopark is one of Indonesia's geoparks, which is located in East Java. A total of 153 bacteria have been isolated from Pelangi Forest, which were then given the isolate code IHP. These bacterial isolates can be utilized in industries, including organic matter decomposer agents, plant biocontrol agents, and probiotics. To ensure these bacteria are safe to use in various fields, they must be non-disease-causing (non-pathogenic). Safety evaluations based on the hemolysis reactions offer simple tests to ease the analysis of potential pathogenic bacteria. The study aimed to evaluate the safety of bacterial isolates from Pelangi Forest for their hemolysis reactions. The hemolysis test was conducted using blood agar media, from which isolates with a negative (Î») reaction. Based on the results of hemolysis tests, 30 out of 153 bacterial isolates (19.60%) were found to be negative reactions. These bacteria are safe to proceed with for potential analysis.